Lateral Meniscus Height and ACL Reconstruction Failure: A Nested Case–Control Study - Tamimi, Iskandar; Enrique, David Bautista; Alaqueel, Motaz; Tat, Jimmy; Lara, Almudena Pérez; Schupbach, Justin; Burman, Mark; Martineau, Paul (The Journal of Knee Surgery, 2021)
Previous work has shown that the morphology of the knee joint is associated with the risk of primary anterior cruciate ligament (ACL) injury. The objective of this study is to analyze the effect of the meniscal height, anteroposterior distance of the lateral tibial plateau, and other morphological features of the knee joint on risk of ACL reconstruction failure. A nested case–control study was conducted on patients who underwent an ACL reconstruction surgery during the period between 2008 and 2015. Cases were individuals who failed surgery during the study period. Controls were patients who underwent primary ACL reconstruction surgery successfully during the study period. They were matched by age (±2 years), gender, surgeon, and follow-up time (±1 year). A morphological analysis of the knees was then performed using the preoperative magnetic resonance imaging scans. The anteroposterior distance of the medial and lateral tibial plateaus was measured on the T2 axial cuts. The nonweightbearing maximum height of the posterior horn of both menisci was measured on the T1 sagittal scans. Measurements of the medial and lateral tibial slope and meniscal slope were then taken from the sagittal T1 scans passing through the center of the medial and lateral tibial plateau. A binary logistic regression analysis was done to calculate crude and adjusted odds ratios (ORs) estimates. Thirty-four cases who underwent ACL revision surgery were selected and were matched with 68 controls. Cases had a lower lateral meniscal height (6.39 ± 1.2 vs. 7.02 ± 0.9, p = 0.008, power = 84.4%). No differences were found between the two groups regarding the bone slope of the lateral compartment (6.19 ± 4.8 vs. 6.92 ± 5.8, p = 0.552), the lateral meniscal slope (–0.28 ± 5.8 vs. –1.03 ± 4.7, p = 0.509), and the anteroposterior distance of the lateral tibial plateau (37.1 ± 5.4 vs. 35.6 ± 4, p = 0.165). In addition, no differences were found in the medial meniscus height between cases and controls (5.58 ± 1.2 vs. 5.81 ± 1.2, respectively, p = 0.394). There were also no differences between cases and controls involving the medial bone slope, medial meniscal slope, or anterior posterior distance of the medial tibial plateau. Female patients had a higher medial (4.8 degrees ± 3.2 vs. 3.3 ± 4.1, p = 0.047) and lateral (8.1 degrees ± 5.1 vs. 5.6 degrees  ± 5.6, p = 0.031) tibial bone slope, and a lower medial (5.3 mm ± 1.0 vs. 6.1 mm ± 1.2, p = 0.001) and lateral (6.6 ± 1.0 vs. 7.0 ± 1.2, p = 0.035) meniscus height, and medial (4.3 ± 0.4 vs. 4.8 ± 0.4, p =0.000) and lateral (3.3 ± 0.3 vs. 3.9 ± 0.4, p = 0.000) anteroposterior distance than males, respectively.The adjusted OR of suffering an ACL reconstruction failure compared to controls was 5.1 (95% confidence interval [CI]: 1.7–14.9, p = 0.003) for patients who had a lateral meniscus height under 6.0 mm. The adjusted OR of suffering an ACL reconstruction failure was 2.4 (95% CI: 1.0–7.7, p = 0.01) for patients who had an anteroposterior distance above 35.0 mm. Patients with a lateral meniscal height under 6.0 mm have a 5.1-fold risk of suffering an ACL reconstruction failure compared to individuals who have a lateral meniscal height above 6.0 mm. Patients with a higher anteroposterior distance of the lateral tibial plateau also have a higher risk of ACL reconstruction failure.
Keywords: anterior cruciate ligament; reconstruction; failure; meniscus; anteroposterior; length; height; risk; morphology; knee